Repetibility of little size and body weigth in rabbit lion borgoña (orictolagus cuniculus) - Bazán Garcia, Augusto (2009)
In ten rabbits of race Leonado of Burgundy was the litter size (CT) and the average weight per litter at weaning (PD) to determine the repeatability of these two parameters, evaluating three consecutive deliveries and analyzed with analysis variance. The estimated values of TC and PD were 0.26 and 0.46 respectively. These findings may be useful for the selection of players.